2019
DOI: 10.1002/jcop.22248
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use and psychological distress in the Native Hawaiian and Pacific Islander adults compared with other racial/ethnic groups: Data from the National Health Interview Survey, 2014

Abstract: Document the prevalence of electronic cigarette (E‐cigarette) use among the native Hawaiian and other Pacific Islander (NHPI) adults compared with other racial/ethnic groups, and examine associations between psychological distress and E‐cigarette use. 2014 National Health Interview Survey (NHIS) and 2014 NHPI–NHIS were combined for comparisons. Data were analyzed using descriptive statistics, Rao‐Scott χ2 test, and multivariable logistic regression. E‐cigarette use among NHPI (5.6%) was significantly higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Of particular concern are NHPIs' elevated prevalence of conventional cigarette use as NHPI adults have been shown to have increased rates of cigarette smoking (Martell et al, 2016)an established e-cigarette risk factor (Chapman & Wu, 2014) compared to other US racial groups. This heightened ecigarette risk is most apparent in a recent dataset where NHPI adults reported higher prevalence of e-cigarette use (5.6%) vs. African Americans (2.1%) and Latinas/os (2.2%) (Narcisse et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Of particular concern are NHPIs' elevated prevalence of conventional cigarette use as NHPI adults have been shown to have increased rates of cigarette smoking (Martell et al, 2016)an established e-cigarette risk factor (Chapman & Wu, 2014) compared to other US racial groups. This heightened ecigarette risk is most apparent in a recent dataset where NHPI adults reported higher prevalence of e-cigarette use (5.6%) vs. African Americans (2.1%) and Latinas/os (2.2%) (Narcisse et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Second, recognizing that often there are not large enough sample sizes of NHPIs collected at the federal level to be reportable or to make informed decisions, we recommend a second round of NHPI NHIS data collection. The 2014 NHPI NHIS has been extensively used to report on NHPI disparities(Narcisse et al 2020). A subsequent iteration of the NHPI NHIS will bolster the sample size and provide more accurate surveillance of NHPI health nationally.Third, when possible, NHPI data should be further disaggregated into subpopulations given the diverse languages, cultural practices, and histories of each of the Pacific Island groups that have been impacted by settler colonialism, militarization, and migration in ways unique to each other.…”
mentioning
confidence: 99%
“…For example, in HI, though 12.3% of all adults report current smoking, the smoking prevalence is highest for NHPIs at 19.7% (Centers for Disease Control & Prevention, 2015). The distribution of e-cigarette prevalence trends in similar directions, with the highest rates found in NHPIs compared to persons of all other racial/ethnic groups (Narcisse et al, 2020). Subica et al (2020) found a substantially higher rate of past month e-cigarette use (39%) among Samoan and Marshallese young adults living in NHPI communities in CA and Arkansas (AR) and data from a Hawaiian sample of adults (Seto et al, 2016) showed that NHs had the highest rates of e-cigarette experimentation compared to participants from other racial/ethnic groups.…”
Section: Tobacco- and E-cigarette-related Racial/ethnic Disparitiesmentioning
confidence: 78%